SUSTAINABLE ART MANAGEMENT IN THE SCOPE OF FOLK ART FESTIVALS - Rahmat, Joey; Sujana, I Wayan; Jodog, I Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
In the ever-evolving evolution of cultural events, the integration of sustainable practices in curatorial and art management is becoming increasingly important. This report explores the application of sustainability strategies in the context of art festivals, examining the intersection between environmental responsibility, cultural preservation, and community engagement. By analyzing case studies of leading art festivals that have successfully adopted sustainability practices, the report identifies key approaches such as resource optimization, waste reduction, and promotion of eco-friendly materials. In addition, the report highlights the role of stakeholders, including artists, organizers, and spectators, in fostering a culture of sustainability. These findings underscore the potential for sustainable arts management that not only reduces the environmental impact of festivals but also increases social and economic impacts. The report aims to provide a comprehensive framework for art festival organizers to integrate sustainability into their planning and implementation processes, ultimately contributing to a more resilient and responsible cultural sector.